2018
DOI: 10.1037/hea0000598
|View full text |Cite
|
Sign up to set email alerts
|

Is fatigue a disease-specific or generic symptom in chronic medical conditions?

Abstract: Fatigue severity can largely be explained by transdiagnostic factors; the associations vary between chronic diseases in strength and significance. This suggests that severely fatigued patients with different chronic diseases can probably benefit from a transdiagnostic fatigue-approach which focuses on individual patient needs rather than a specific disease. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
95
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(111 citation statements)
references
References 40 publications
10
95
0
2
Order By: Relevance
“…However, the findings regarding loneliness, time, language and strategies to manage fatigue are less recognised and should inform future interventions. A recent study indicates that we may not require disease-specific approaches as the severity of fatigue can largely be explained by transdiagnostic factors 39. Thus, we may develop interventions to help reduce fatigue for people with different chronic diseases targeting individual needs 39.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the findings regarding loneliness, time, language and strategies to manage fatigue are less recognised and should inform future interventions. A recent study indicates that we may not require disease-specific approaches as the severity of fatigue can largely be explained by transdiagnostic factors 39. Thus, we may develop interventions to help reduce fatigue for people with different chronic diseases targeting individual needs 39.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study indicates that we may not require disease-specific approaches as the severity of fatigue can largely be explained by transdiagnostic factors 39. Thus, we may develop interventions to help reduce fatigue for people with different chronic diseases targeting individual needs 39. Furthermore, the specific cognitive processes should be mapped and targeted 40…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in adults, the incidence and severity of fatigue was found to exist rather independently from the somatic diagnosis 7. This emerging concept has not yet been studied in children and adolescents, although it has been reported that fatigue can persist despite low disease activity 7–9.…”
Section: Introductionmentioning
confidence: 99%
“…Fatigue is one of the most common symptoms of patients seeking professional care (Stadje et al 2016;Menting et al 2018) and common cause of lost working hours (Ricci et al 2007;Deligkaris et al 2014). Yet, we understand little of its underlying mechanisms (Gergelyfi et al 2015).…”
Section: Introductionmentioning
confidence: 99%